Clinical features and management of haemophilic pseudotumours: a single US centre experience over a 30‐year period. (31st October 2013) - Lim, M. Y.; Nielsen, B.; Ma, A.; Key, N. S.
Summary Given the rarity of haemophilic pseudotumours, consensus on management is lacking. We describe the clinical features and management of haemophilic pseudotumours by retrospectively reviewing the medical records of haemophilia patients with a diagnosis of pseudotumour seen at our Hemophilia Center from 1981 to 2011. We recorded the following data: type and severity of haemophilia, documented aetiological antecedent, localization of the pseudotumour, presenting symptoms, management and outcome. We identified 12 pseudotumours in 11 patients over a 30‐year period. Six patients had known inhibitors or a history of inhibitor. An aetiological antecedent leading to the development of pseudotumour was reported in nine cases. Localization of the pseudotumour was confined to soft tissue (n = 3) and bone (n = 8). Six of the 12 pseudotumours (50%) were not diagnosed at the time of initial presentation, with a delay ranging from 6 weeks to 6 years. In eight cases, surgical intervention (surgical drainage, n = 2; excision, n = 4; limb amputation, n = 2) was the initial treatment choice, with complete resolution in six cases. Conservative management with close monitoring occurred in three cases, with one case subsequently requiring surgical resection. We conclude that haemophilic pseudotumours still occur sporadically, and the diagnosis is frequently delayed. Surgical intervention is generally a safe and effective treatment, although conservative management may be appropriate in selected cases.